Analisis Penambahan Larutan Gula Terhadap Kuat Tekan dan Kuat Lentur Beton yang Mengandung Arang Briket - Fortuna, Anisa Feby; Sariman, Syahrul; Hijriah, Hijriah (Program Studi Teknik Sipil Universitas Bosowa, 2023)
Concrete is frequently used as the primary component of building construction. Given its role as a former, concrete plays a significant role in the construction industry. To make pozzolanic concrete more useful as a mineral ingredient for concrete, coal briquette charcoal ash, and sugar solution are added to the mixture. The aim of this study was to determine the impact on concrete's compressive strength and flexural strength by adding 0.10%, 0.20%, and 0.30% sugar solution containing 5% charcoal briquettes. There were 39 specimen samples, including 16 samples of variance concrete and 23 samples of regular concrete. Concrete on the test object is treated by immersing it for 28 days. When the specimen was 28 days old, the concrete's compressive and flexural strengths were evaluated. According to the test's findings, variation concrete has greater compressive and flexural strengths than regular concrete. The compressive strength and flexural strength of the concrete mixture increase with the amount of sugar solution added